A Nanoparticle-Lectin Immunoassay Improves Discrimination of Serum CA125 from Malignant and Benign Sources. (6th January 2020) - Gidwani, Kamlesh; Huhtinen, Kaisa; Kekki, Henna; van Vliet, Sandra; Hynninen, Johanna; Koivuviita, Niina; Perheentupa, Antti; Poutanen, Matti; Auranen, Annika; Grenman, Seija; Lamminmäki, Urpo; Carpen, Olli; et al.
Abstract: BACKGROUND: Measurement of serum cancer antigen 125 (CA125) is the standard approach for epithelial ovarian cancer (EOC) diagnostics and follow-up. However, the clinical specificity is not optimal because increased values are also detected in healthy controls and in benign diseases. CA125 is known to be differentially glycosylated in EOC, potentially offering a way to construct CA125 assays with improved cancer specificity. Our goal was to identify carbohydrate-reactive lectins for discriminating between CA125 originating from EOC and noncancerous sources. METHODS: CA125 from the OVCAR-3 cancer cell line, placental homogenate, and ascites fluid from patients with cirrhosis were captured on anti-CA125 antibody immobilized on microtitration wells. A panel of lectins, each coated onto fluorescent europium-chelate–doped 97-nm nanoparticles (Eu +3 -NPs), was tested for detection of the immobilized CA125. Serum samples from high-grade serous EOC or patients with endometriosis and healthy controls were analyzed. RESULTS: By using macrophage galactose-type lectin (MGL)-coated Eu +3 -NPs, an analytically sensitive CA125 assay (CA125 MGL ) was achieved that specifically recognized the CA125 isoform produced by EOC, whereas the recognition of CA125 from nonmalignant conditions was reduced. Serum CA125 MGL measurement better discriminated patients with EOC from endometriosis compared to conventional immunoassay. The discrimination was particularly improved for marginally increased CA125 values and for earlier detection of EOC progression. CONCLUSIONS: The new CA125 MGL assay concept could help reduce the false-positive rates of conventional CA125 immunoassays. The improved analytical specificity of this test approach is dependent on a discriminating lectin immobilized in large numbers on Eu +3 -NPs, providing both an avidity effect and signal amplification.